Pengaruh Perilaku Konsumen Terhadap Keputusan Pembelian Kue Khas Ternate (Bagea, Makron dan Roti Kenari) - Alhadar, Lidia Ferial; Sirat, Abdul Hadi (Jurnal MS, 2023)
The purpose of this study is to know and analyze: (1) The influence of cultural factors on buying decisions typical of Ternate; (2) The influence of social factors on the purchase decision of the typical cake of Ternate; (3) The influence of personal factors on buying decisions typical of Ternate; (4) Influence of psychological factor to decision of purchasing cake typical of Ternate; and (5) The influence of cultural, social, personal and psychological factors on the buying decision of Ternate cakes simultaneously. Methodology: The test equipment used is multiple regression analysis using statistical package for social scientists (SPSS) as a statistical test tool. The number of samples of the study were 100 consumers. Finding: H1, H2, H3, H5, and H5 are accepted at the 5% confidence level. Conclusion: The results showed that: (1) Cultural factors (X1) have a positive and significant effect partially on the purchase decision of typical cakes ternate. These results are based on t arithmetic values greater than t table values and smaller significance values than alpha; (2) Social factors (X2) have a positive and partially significant effect on buying decision of typical cakes of ternate. This result is based on a larger F count value and a smaller significance value than the alpha value; (3) Personal factors (X3) have a positive and partially significant effect on buying decision of Ternate typical cake. This result is based on a larger F count value and a smaller significance value than the alpha value; (4) psychological c factors (X4) have a positive and partially significant effect on buying decision of Ternate typical cake. This result is based on a larger F count value and a smaller significance value than the alpha value; and (5) Cultural factors, social factors, personality factors, and psychological factors have a positive and significant influence simultaneously on the decision to purchase a typical cake Ternate.